643 Risk factors for the development of work related musculoskeletal disorders among information technology professionals. (24th April 2018) - Sharan, Deepak; Rajkumar, Joshua Samuel
Abstract : Introduction: Work Related Musculoskeletal Disorders (WRMSD) are highly prevalent among Information Technology (IT) professionals. However, the risk factors associated with the development of WRMSD are not clear. Hence, the objective of this study was to evaluate the risk factors that predispose IT professionalsto the development of WRMSD. Methods: A prospective analysis of 7280 employees of a single IT company in an Industrially Developing Country was conducted. Among them, 5210 were males and 2070 were females, between the ages 20 to 60 years. The employees were evaluated by a detailed questionnaire consisting of demographic data, job details, health status, physical risk factors, short-form Work Style Questionnaire and Nordic Musculoskeletal Pain Questionnaire. The data were extracted and statistical analysis was done. Result: The mean age of the employees was 32.5 years.58% of the employees were diagnosed by an experienced occupational health physician (OHP) to have a WRMSD, which predominantlyincluded myofascial pain syndrome of the neck, upper and lowerback. Age, Body Mass Index (BMI), working hours and work-style were positively correlated (r<0.01) with the presence of WRMSDs, as higher the age and BMI, increased working hours and higher work-style score showed higher prevalence of WRMSD. On the other hand, rest breaks during work, regular exercises and formal ergonomics training were negatively correlated (r<−0.01) with the presence of WRMSDs, as more frequent breaks, regular exercises and ergonomics training showed lower prevalence of WRMSD. Also, the presence of co morbidities like diabetes, hypothyroidism and osteopenia/osteoporosis had a positive influence on the prevalence of WRMSDs in the study population. Other specific factors like work experience, hand dominance, type of computer used also had an influence on the development of WRMSDs. Discussion: The risk factor analysis gives an insight to the appropriate areas of ergonomic interventions among IT professionals.